Film Aceh dalam Perspektif Etika Komunikasi Islam - Al Zuhri; Heri Rahmat Syahputra (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2021)
The goal of this study was to look at the use of ethics in Aceh's cinema, namely, as an area of Islamic law. Qualitative content analysis with an explanatory approach was employed as the strategy. Meanwhile, documentation were employed to obtain data. The study's focus is on audiovisual items of Aceh movie video compact disc, "Zainab Section 2". The study's findings suggest that the movie "Zainab Section 2" failed to convey themes that are consistent with Islamic communication principles. Even if there are, they are in the minority. There is a lot of lameness in Islamic communication ethics, according to the author. Furthermore, this film lacks a specific personality that distinguishes it from works outside the region, has gotten little government attention, and does not prioritize the presentation of educational and da'wah aspects. As a result, the presence of a particular movie censorship institution in Aceh is extremely vital for the future orientation of Acehnese cinema, given that, in addition to being able to have positive effects, films may undeniably have detrimental impacts on the audience. And good cooperation is needed from various parties, be it the government, universities, media crews, artists, and elements of society. So, it is hoped that in the end, the enforcement of Islamic law in Aceh can immediately touch the movie aspect.